The Effect of Computer-Based Music Education Software on the Identification of Note-Names - Lim, Zek Chew (2004)

(untitled)
This study investigated the effect of computer-based music education software application on the identification of note-names. The study sought to ascertain the achievement of non-music major trainee teachers on the learning of note-names and their attitudes towards learning music in general. A randomized posttest-only control group experimental design was used in this investigation. The sample consisted of 62 semester 1 trainee teachers who were studying in a music elective class at a teacher training college. The trainee teachers were divided into two equal groups and both the groups completed a 12-hour course. The first group comprised 31 trainee teachers who made up the control group that received instructions from a lecturer. The remaining 31 trainee teachers formed the second group that learnt the same content using computer-based music education software comprising Music Ace, A Musical Tutorial 2.0 and Musical Space Invaders v1.0. The activities planned in the course were parallel for both groups in terms of content and time allocation for each topic. Four research instruments were used to collect data at the end of the course. The ability on note-names identification was evaluated in three methods: Recognition of Note-Names on the Staff Test (RNNS), Keyboard Matching of Note-Names Test (KMNN) and Keyboard Sight Reading Test (KSRT). A questionnaire was administrated to generate data required to look into the attitude of the trainee teachers toward the learning of music in general. Findings in this study evidently revealed positive effects of computerbased music education software application in the teaching of reading note-names. The overall result from the Recognition of Note-Names on the Staff Test [q60)=3.20, p=.002], Keyboard Matching of Note- Names Test [t(60)=5.69, p=.000] and Keyboard Sight Reading Test favouring computer application was reported. However, when subsections were analysed, t-test results in Recognition of Note-Names on the Staff Test of one note-name and two note-names showed no difference in the achievement tests. As for other subsections in Recognition of Note-Names on the Staff Test and Keyboard Matching of Note-Names Test, significant differences favouring the computerbased music education group were reported. The mean difference of each subsection for both tests increased in value as the difficulty level of the test increased. Results from the Keyboard Sight Reading Test revealed that trainee teachers from both groups performed equally well in the note accuracy test but the time taken by the computerbased music education group to complete all the exercises on the keyboard was shorter than the control group. Findings from the study revealed that the ability to read note-names in a faster speed may be increased with the support of computer-based music education software. Analysis of the Attitude towards Learning Music Questionnaire revealed that majority of the trainee teachers had positive attitudes towards music as a subject in this study though there was simcant difference statistically in the t test result. The result t(60)=0.251, p.039 obtained was statistically simcant at -05 level. Evidently, the results of this study indicated that a wider usage of computer-based music education software in the Malaysian context would bring positive results in trainee teachers' achievement levels and interest.